2021
DOI: 10.3390/jcm10102101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ageing on Clinical, Hormonal and Sonographic Features Associated with PCOS—A Long-Term Follow-Up Study

Abstract: The knowledge of polycystic ovary syndrome (PCOS) natural history is limited. Our objective was to assess the effect of aging on clinical, hormonal and sonographic ovarian PCOS features and additionally to identify parameters that impact the course of PCOS. A secondary aim was to supply additional information on the reproductive outcome in women with previously diagnosed PCOS. A longitudinal cohort study with a median follow-up of 120.9 months was conducted, and 31 Caucasian women previously diagnosed with PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 108 publications
(130 reference statements)
1
5
0
Order By: Relevance
“…For instance, women without persistent ovulatory dysfunction were older than women with persistent ovulatory dysfunction. Similarly, other studies have reported shorter and more regular menstrual cycle lengths in women with PCOS as they were getting older 41,42 . Also, postprandial glucose and high‐density lipoprotein levels were statistically different according to persistent ovulatory dysfunction (Table 1).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…For instance, women without persistent ovulatory dysfunction were older than women with persistent ovulatory dysfunction. Similarly, other studies have reported shorter and more regular menstrual cycle lengths in women with PCOS as they were getting older 41,42 . Also, postprandial glucose and high‐density lipoprotein levels were statistically different according to persistent ovulatory dysfunction (Table 1).…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, other studies have reported shorter and more regular menstrual cycle lengths in women with PCOS as they were getting older. 41,42 Also, postprandial glucose and high-density lipoprotein levels were statistically different according to persistent ovulatory dysfunction (Table 1). However, they did not demonstrate any statistical significance (p = 0.21 and 0.15, respectively) in likelihood ratio tests after they were added to Model 3.…”
Section: Discussionmentioning
confidence: 98%
“…The fertility window of PCOS patients may extend to 40 years of age, but at ages, over 40 years old come declining ovarian reserve, the poor effect of ovulation-stimulating treatments, and a low pregnancy rate [ 19 ]. Despite serum AMH decreases over time in all of the women, the decrease in the PCOS patients was less pronounced than in controls, and this may suggest better preservation of the ovarian reserve and thus a prolonged reproductive life span [ 20 ]. A study showed that the live birth rate and cumulative live birth rate in PCOS patients aged 35–40 years were significantly higher than in the control group [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is associated with central obesity, dyslipidemia, hypertension, and insulin resistance ( 7 ), which all have been described to decrease BD ( 8 , 9 , 10 , 11 ). However, hyperandrogenism, one of the key diagnostic criteria of PCOS, could have a protective effect on BD ( 12 ). Furthermore, PCOS is associated with prolonged menopause which could lead to longer estrogen exposure and may result in a delay of loss of BD ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%